Spectral efficiency and performance improvement of coherent optical transmission system - Muthanna Ali Kadhim; Ali Yousif Fattah; Atheer Alaa Sabri (Institute of Advanced Engineering and Science, 2022)
This paper presents an orthogonal frequency division multiplexing (OFDM) for a long-haul optical transmission system with high-rate transferability to alleviate dispersion effects. In addition, we suggest combining polarization division multiplexing (PDM) with coherent OFDM (CO-OFDM) to increase spectral efficiency (SE). Based on OptiSystem (2021) version 18.0